2021
DOI: 10.1109/jstars.2021.3114116
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Long-Term Expansion and Dieback of Spartina Alterniflora Using Google Earth Engine and Object-Based Hierarchical Random Forest Classification

Abstract: The overwhelming spread of Spartina alterniflora (smooth cordgrass) over recent decades has put many native plant communities and coastal environments at risk. Therefore, longterm monitoring of S. alterniflora dynamics is necessary to better understand and manage the invasion of the species. However, it is difficult to map Spartina saltmarshes in China on an annual or multiyear epoch basis. To address this issue, we developed a classification approach integrating Google Earth Engine (GEE) and object-based hier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…The DMNNR was considered to be the first and largest wildlife nature reserve in the world for Elaphurus davidianus (Père David's deer). The Ramsar Wetland Convention Organization designated the DMNNR as a wetland of international importance, in 2002 (Lu et al, 2018;Yan et al, 2021). The present study took the third core area of DMNNR and its tidal flat as the research area (25 km 2 ), which silted up in the last 30 years (Figure 1).…”
Section: Study Areamentioning
confidence: 93%
See 4 more Smart Citations
“…The DMNNR was considered to be the first and largest wildlife nature reserve in the world for Elaphurus davidianus (Père David's deer). The Ramsar Wetland Convention Organization designated the DMNNR as a wetland of international importance, in 2002 (Lu et al, 2018;Yan et al, 2021). The present study took the third core area of DMNNR and its tidal flat as the research area (25 km 2 ), which silted up in the last 30 years (Figure 1).…”
Section: Study Areamentioning
confidence: 93%
“…A total of 2.5 km of small dykes and 10 km of artificial freshwater ditches were built to meet the needs of various wild animals and to control the spread of S. alterniflora (Figure 1). DMNNR reported that the number of wild E. davidianus individuals increased from 9 in 1999 to 1820 in 2020, which resulted in a decrease in S. alterniflora by foraging and trampling (Yan et al, 2021).…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations